PENERAPAN PROGRAM RUMAH PANGAN LESTARI DI KOMPLEK PERUMAHAN BTN BINA HARAPAN DAN PERUMNAS UNIB KOTA BENGKULU - Puji Harsono; Bambang Sumantri; Prasetyo Prasetyo (Universitas Bengkulu, 2018)
Strengthening food security can be started at the household level, one way is through the program Sustainable Food House (RPL). Sustainable Food Houses Program in urban residential areas is one way of creative, innovative and environmentally friendly to realize the green area in the yard of a residential beautiful, cool and productive. How this is done by utilizing the pot wheelbase (wick pot) on a semi-organic vegetable production. IbM activities of community groups to inspire citizens and public housing complexes around the housing to apply RPL through the pot wheelbase in the cultivation of vegetables in home gardens urban areas. Utilization of open space with vegetable crops, in addition to economic value, it also creates a healthy and educational environment for the citizens housing complex BTN Hope and Housing Development UNIB. The results of the activities IbM the RPL program is able to evoke the spirit of the citizens in an effort to greening the housing area. This is evidenced by the use of the home page and all along the road on both the housing. It also provides technical skills of residents in the cultivation of vegetables in the pot so that the need for some types of vegetables for his family adequately met from the application of science and technology activities for the community by a team of professors from the University of Bengkulu. Keywords: green areas, sustainable food home, wick pot, vegetables